(3GdLhgQ GdKejf aj SjQ Gdedhc hGdSdGWjfs - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s ((3GdbGgQI GdeMQhSI s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf CeG HYO jbhd Hf ObeGb gPG cJGH LeYJ ajg CNHGQ GdNdaGA GdQGTOjf hSejJg GdLhgQ GdKejf ai SjQ Gdedhc hGdSdGWjf hGHJOCJ HSjOi CHj HcQ GdUOjb QVi Gddg Yfg s
(3BNQgG (B:s
(3hNjQGJ eSJeQg hajgG NWH ddSdWGf ai HZOGO heG QOjf hGdehUd ceG bjd hGddg JYGdi CYde hGdMeO ddg hMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B86s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B619s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJGQjNs